Effects of a microencapsulated formula of organic acids and essential oils on nutrient absorption, immunity, gut barrier function, and abundance of enterotoxigenic Escherichia coli F4 in weaned piglets challenged with E. coli F4. (11th August 2020) - Choi, Janghan; Wang, Lucy; Liu, Shangxi; Lu, Peng; Zhao, Xiaoya; Liu, Haoming; Lahaye, Ludovic; Santin, Elizabeth; Liu, Song; Nyachoti, Martin; Yang, Chengbo
Abstract: The objective was to study the effects of microencapsulated organic acids (OA) and essential oils (EO) on growth performance, immune system, gut barrier function, nutrient digestion and absorption, and abundance of enterotoxigenic Escherichia coli F4 (ETEC F4) in the weaned piglets challenged with ETEC F4. Twenty-four ETEC F4 susceptible weaned piglets were randomly distributed to 4 treatments including (1) sham-challenged control (SSC; piglets fed a control diet and challenged with phosphate-buffered saline (PBS)); (2) challenged control (CC; piglets fed a control diet and challenged with ETEC F4); (3) antibiotic growth promoters (AGP; CC + 55 mg·kg –1 of Aureomycin); and (4) microencapsulated OA and EO [P(OA+EO); (CC + 2 g·kg −1 of microencapsulated OA and EO]. The ETEC F4 infection significantly induced diarrhea at 8, 28, 34, and 40 hr postinoculation (hpi) ( P < 0.05) in the CC piglets. At 28 d postinoculation (dpi), piglets fed P(OA+EO) had a lower ( P < 0.05) diarrhea score compared with those fed CC, but the P(OA+EO) piglets had a lower ( P < 0.05) diarrhea score compared with those fed the AGP diets at 40 dpi. The ETEC F4 infection tended to increase in vivo gut permeability measured by the oral gavaging fluorescein isothiocyanate-dextran 70 kDa (FITC-D70) assay in the CC piglets compared with the SCC piglets ( P = 0.09). The AGP piglets had higher FITC-D70 flux than P(OA+EO) piglets ( P < 0.05). The ETEC F4 infection decreased mid-jejunal VH in the CC piglets compared with the SCC piglets ( P < 0.05). The P(OA+EO) piglets had higher ( P < 0.05) VH in the mid-jejunum than the CC piglets. The relative mRNA abundance of Na + -glucose cotransporter and B 0 AT1 was reduced ( P < 0.05) by ETEC F4 inoculation when compared with the SCC piglets. The AGP piglets had a greater relative mRNA abundance of B 0 AT1 than the CC piglets ( P < 0.05). The ETEC F4 inoculation increased the protein abundance of OCLN ( P < 0.05), and the AGP piglets had the lowest relative protein abundance of OCLN among the challenged groups ( P < 0.05). The supplementation of microencapsulated OA and EO enhanced intestinal morphology and showed anti-diarrhea effects in weaned piglets challenged with ETEC F4. Even if more future studies can be required for further validation, this study brings evidence that microencapsulated OA and EO combination can be useful within the tools to be implemented in strategies for alternatives to antibiotics in swine production.